Покчи гужем: кылбуръёс / Владимир Романов - Романов Владимир Васильевич (Удмуртия, 1975)
Экземпляры: ЧЗ (20160414) / Инвентарный номер: 57142 / Цена: 0.28 / Сис.шифр: С(Удм) / Авт.знак: Р 69 / ГРНТИ: 17.82.10 / ББК: С(Удм)